Evolving Roles for Patients as Partners in a National Kidney Health Research Network: A Qualitative Study. - Melika‐Abusefien, Mark; Fernandez, Nicolas; Miranda, Keila Turino; Jones, Jocelyn M.; Talson, Melanie D.; Pokiak, Letitia; Allu, Selina; Wysocki, Julie; James, Matthew T.; Elliott, Meghan J. (Health Expectations, 2026)
Introduction: Patient partnerships are central to all activities of the patient‐oriented kidney health research network, Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can‐SOLVE CKD). The aim of this study was to characterise how patient partner roles in the network and the structures that influence their engagement have evolved over time. Methods: We conducted a secondary analysis of two qualitative datasets involving focus groups and interviews exploring perspectives on patient engagement within the network (Study A, N = 48) and a series of workshops defining network strengths and priorities related to inclusivity, diversity, equity and accessibility pillars (Study B, N = 49). We analysed all data from the primary studies, including deidentified transcripts (Study A) and virtual 'sticky notes' (Study B), using inductive thematic analysis, which involved coding data in duplicate and developing themes that captured shifts in perspectives on patient partner roles. Results: Data from a total of 97 participants (40 patient partners, 43 researchers and/or clinicians and 14 network operational staff) were included in this secondary qualitative analysis. We identified three main themes: (1) Shift from traditional to emerging roles—initial roles defined by engagement frameworks were superseded by novel roles involving advocacy, outreach and mentorship; (2) Distinguishing role delegation from self‐determination—roles became increasingly active and shaped by patient partner‐identified gaps or interests; (3) Strengthening supports for meaningful patient contribution—structures for meaningful engagement grew more formalised and emphasised integration of diverse perspectives. Conclusions: The shift in roles and supports for patient partners within the Can‐SOLVE CKD Network reflects a broader movement toward more collaborative, influential and equitable research partnerships. Our findings have implications for large‐scale research teams and networks seeking to foster and sustain authentic patient engagement over time. Patient and Public Contribution: This study was undertaken in collaboration with partners with experience of kidney disease (N.F.), Indigenous advocacy related to kidney health (L.P.) and kidney policy and program development (J.W.), as well as Can‐SOLVE CKD network staff and committee members (K.T.M., J.M.J., M.D.T., S.A.). N.F. conceived and co‐led data collection and analysis in the original qualitative study. L.P. and J.W. were working group members for the IDEA project. The patient partners and network members contributed meaningful insights that shaped our approach, interpretation and presentation of findings from this secondary qualitative analysis.